Development and characterization of a new TILLING population of common bread wheat (Triticum aestivum L.). - Liang Chen; Linzhou Huang; Donghong Min; Andy Phillips; Shiqiang Wang; Pippa J Madgwick; Martin A J Parry; Yin-Gang Hu (PLoS ONE)
Mutagenesis is an important tool in crop improvement. However, the hexaploid genome of wheat (Triticum aestivum L.) presents problems in identifying desirable genetic changes based on phenotypic screening due to gene redundancy. TILLING (Targeting Induced Local Lesions IN Genomes), a powerful reverse genetic strategy that allows the detection of induced point mutations in individuals of the mutagenized populations, can address the major challenge of linking sequence information to the biological function of genes and can also identify novel variation for crop breeding. Wheat is especially well-suited for TILLING due to the high mutation densities tolerated by polyploids. However, only a few wheat TILLING populations are currently available in the world, which is far from satisfying the requirement of researchers and breeders in different growing environments. In addition, current TILLING screening protocols require costly fluorescence detection systems, limiting their use, especially in developing countries. We developed a new TILLING resource comprising 2610 M(2) mutants in a common wheat cultivar 'Jinmai 47'. Numerous phenotypes with altered morphological and agronomic traits were observed from the M(2) and M(3) lines in the field. To simplify the procedure and decrease costs, we use unlabeled primers and either non-denaturing polyacrylamide gels or agarose gels for mutation detection. The value of this new resource was tested using PCR with RAPD and Intron-spliced junction (ISJ) primers, and also TILLING in three selected candidate genes, in 300 and 512 mutant lines, revealing high mutation densities of 1/34 kb by RAPD/ISJ analysis and 1/47 kb by TILLING. In total, 31 novel alleles were identified in the 3 targeted genes and confirmed by sequencing. The results indicate that this mutant population represents a useful resource for the wheat research community. We hope that the use of this reverse genetics resource will provide novel allelic diversity for wheat improvement and functional genomics.